Epidemiologic study of cluster headache prevalence in a medium-size city in Brazil - Jurno, Mauro E.; Pereira, Bárbara S. R.; Fonseca, Felipe A. S.; Teixeira, Gabriel A.; Maffia, Ludimila Q.; Barros, Maria R. A.; Camilo, Vívian F.; Bordini, Carlos A. (Arquivos de Neuro-Psiquiatria, 2018)
To determine the prevalence of cluster headache (CH) in Barbacena, a medium-size city in the State of Minas Gerais, Brazil. Methods The total population of Barbacena is 126,284 inhabitants and the Family Health Strategy Program covers 84,610 of them. In order to identify patients with cluster headache, 36,145 of these inhabitants were screened, following which, a questionnaire was completed by 181 health agents distributed throughout the 28 health posts belonging to the Family Health Strategy network. The completed questionnaires were selected based on the clinical criteria established by the International Headache Society, and those patients (18 years of age or older) with a possible CH diagnosis were later assessed by a headache specialist. This was an observational, cross-sectional study.Results In all, 15 patients were diagnosed as having CH, comprising a prevalence of 0.0414%; or 41.4/100,000 inhabitants.Conclusion The prevalence of cluster headache in Barbacena was lower than that observed in many locations worldwide.
Keywords: prevalence; epidemiology; cluster headache; family health strategy